2017
DOI: 10.1002/tesj.328
|View full text |Cite
|
Sign up to set email alerts
|

Spelling It Out, One por Uno: Patterns of Emergent Bilinguals in a Dual Language Classroom

Abstract: The extant research literature on emergent bilingual spelling focuses on developmental patterns and the interference of first language with second language. The purpose of this article is to provide teachers with an alternate view of emergent bilingual spelling in an effort to influence spelling instruction in the classroom. Writing samples produced by second‐grade students in a dual language program were analyzed to gain insight into the spelling development of emergent bilinguals. Strikingly, there was an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Of the errors made by bilingual children from the Spanish-literacy group, 29% were Spanish-influenced. Linan-Thompson et al (2018) found an even higher rate of Spanish-influenced spelling errors in second grade students' bilingual journals (naturalistic writing). They note that over half of the children's spelling errors involved vowels, such as "geyme" for "game.…”
Section: The Acquisition Of Orthography Among Child (Bilingual) Spanimentioning
confidence: 87%
“…Of the errors made by bilingual children from the Spanish-literacy group, 29% were Spanish-influenced. Linan-Thompson et al (2018) found an even higher rate of Spanish-influenced spelling errors in second grade students' bilingual journals (naturalistic writing). They note that over half of the children's spelling errors involved vowels, such as "geyme" for "game.…”
Section: The Acquisition Of Orthography Among Child (Bilingual) Spanimentioning
confidence: 87%
“…For example, because English and Spanish are both alphabetic languages that share many of the same sounds, studies of Spanish-English bilingual children learning two languages simultaneously suggest similar writing progressions in both languages and reciprocal interactions between the languages across time (Butvilofsky et al, 2017). For Alvaro, who is learning Spanish and English sequentially, increasing knowledge in the second language can help him acquire stronger phonemic awareness knowledge (Raynolds & Uhry, 2010), which will be important to both L1 and L2 spelling development (Linan-Thompson et al, 2018). Although teachers cannot possibly know all the intricacies of the varied languages that children might bring to the classroom, a deep appreciation for these cultural and linguistic resources can help them attend to the varied manner in which children's meaning and print-based writing processes support each other.…”
Section: Valuing Children's Linguistic Resourcesmentioning
confidence: 99%
“…Students experimented with letters and words and eventually moved toward the act of spelling by making connections between graphemes and phonemes in both languages. Additionally, Linan‐Thompson et al (2018) found that fluency in English orthography resulted in a decrease in Spanish‐influenced errors. This is substantial because it showed that spelling errors are not a result of language interference but are part of a developmental process of learning to spell that exists across a continuum.…”
Section: Spelling Development With Emergent Bilingualsmentioning
confidence: 99%
“…The software assisted Salomon with English spelling, which allowed him to continue writing and not be frustrated with the choice of letters for the word bed. As part of the repeated exposure to standard spellings of English words, some students began to identify patterns within words that support emergent bilinguals' writing in English (Linan- Thompson et al, 2018).…”
Section: Basic Spelling Supportmentioning
confidence: 99%